2005
DOI: 10.1111/j.1442-2042.2005.01074.x
|View full text |Cite
|
Sign up to set email alerts
|

Superselective embolization of bladder arteries in the treatment of intractable bladder haemorrhage

Abstract: Bladder hemorrhage following radiation therapy is a serious complication in patients undergoing this treatment. Several methods have been proposed to control this particular situation; however, results have been far from satisfactory, with the exception of drastic measures such as hypogastric artery ligation and radical cystectomy. We recently used a method of superselective embolization of the bladder arteries which enabled us to control severe intractable bleeding in a patient submitted to bladder irradiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 6 publications
(6 reference statements)
0
30
1
9
Order By: Relevance
“…Non surgical techniques used to manage haematuria in this setting include irrigation with silver nitrate or formalin, aminocaproic acid treatment, and the application of intravesical hydrostatic pressure. However success rates using these methods are variable and may necessitate a general anaesthetic (5,6). These patients are often not suitable for more radical surgical options such as hypogastric artery ligation, urinary diversion or cystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Non surgical techniques used to manage haematuria in this setting include irrigation with silver nitrate or formalin, aminocaproic acid treatment, and the application of intravesical hydrostatic pressure. However success rates using these methods are variable and may necessitate a general anaesthetic (5,6). These patients are often not suitable for more radical surgical options such as hypogastric artery ligation, urinary diversion or cystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Embolizations of the entire internal iliac artery or arteries to treat radiation-induced HC were reported with successful results; however, serious complications following embolization of the bilateral internal arteries have been reported (5,7,8). Superselective vesical artery embolization has been used as a therapeutic strategy of HC secondary to radiation therapy, trauma, and tumors without ischemic complications (5,6,9,10). The patient in this study showed gradual decline of hematuria after superselective embolization of bilateral inferior vesical arteries and eventual stoppage of hematuria without ischemic complications.…”
Section: Discussionmentioning
confidence: 78%
“…Superior vesical arteries were preserved to prevent ischemic complications, such as bladder necrosis. Superselective embolization of inferior vesical arteries can also prevent ischemic complications, such as gluteal pain or necrosis, genital injury, or tissue necrosis (5,6). Embolizations of the entire internal iliac artery or arteries to treat radiation-induced HC were reported with successful results; however, serious complications following embolization of the bilateral internal arteries have been reported (5,7,8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations